Effect of 410 nm Diode Laser Irradiation on the Growth of Burn Wounds-associated Bacteria, Pseudomonas Aeruginosa and Staphylococcus Aureus - Mohammed, Muna G.; Maki, Amel M. (Iraqi Journal of Laser, 2018)
The effect of 410nm with 100 mW output power and one centimetre spot size (0.128 W/cm2 power density) Diode laser irradiation at different exposure times on the growth of Gram-negative Pseudomonas aeruginosa and Gram-positive Staphylococcus aureus was evaluated. Seventy swap samples were collected from burn and infected wounds of 35 patients admitted to the burn-wound unit in Al-Yarmouk Teaching Hospital in Baghdad during the period from December 2014 to February 2015. These bacteria were isolated and identified depending on their growth on selective media, cultural characteristics, Gram stain morphology and biochemical tests and finally were confirmed by Vitek 2 compact system test .Susceptibility of bacterial isolates to 15antibiotics was tested using the disk diffusion method. Bacterial standard suspension of 108 cell/ml was prepared for P. aeruginosa and S. aureus. Dilutions of 10-6 cell/ml for P. aeruginosa and 10-5 cell/ml for S. aureus were selected. Ten replicates were used for each experimental group. Following irradiation, CFU/ml was calculated, and antibiotic susceptibility test was performed for the most resistant isolate for each bacterial species. From the results, it was found that out of the 70 samples, 17 isolates (24.3%) were P. aeruginosa and 9 isolates (12.9%) were S. aureus. Antibiotic susceptibility test showed that all isolates of P. aeruginosa and S. aureus were multidrug resistant. It was shown that laser irradiation did not affect the susceptibility of P. aeruginosa isolate to all antibiotics tested. However, a slight increase in the susceptibility of S. aureus isolate to Ampicillin/Cloxacillin, Tetracycline and Vancomycin was observed. Laser Irradiation experiments showed that the number of CFU/ml of P. aeruginosa and S. aureus was significantly reduced with increasing exposure times, reaching a100% bacterial mortality at 13 minutes for S. aureus and 19 minutes for P. aeruginosa. In conclusion, the blue laser irradiation seems to have more bactericidal effect on Gram-positive bacteria (S. aureus) than on Gram-negative (P. aeruginosa).